#18: Brincidofovir for the Treatment of Disseminated Human Adenovirus Infection in Pediatric Solid-organ Transplant Recipients. (26th March 2021) - Londeree, Jackson; Garro, Rouba; Romero, Rene; George, Roshan; Winterberg, Pamela; Liverman, Rochelle; Serluco, Anastacia; Shin, Stella; Yildirim, Inci
Abstract: Background: Human adenovirus (HAdV) viremia can cause significant morbidity among pediatric patients undergoing solid-organ transplantation (SOT). Currently, there are no US Food and Drug Administration (FDA)-approved treatments for HAdV infections, and historically the mainstay of treatment has been decreasing immunosuppression with antiviral therapies reserved for those with severe disease. Brincidofovir (BCV) is an investigational antiviral drug with potency against HAdV. We describe four cases of disseminated HAdV infection treated with (BCV) among pediatric SOT patients. Methods: We retrospectively reviewed 4 cases of severe disseminated HAdV infection, which occurred between 2018 and 2019, in a tertiary pediatric transplant center. HAdV infection was defined as a positive HAdV PCR from a clinical specimen. Baseline clinical characteristics, disease course, treatment, and outcomes were reviewed. Results: Four pediatric SOT patients (2 kidneys, 1 dual kidney/liver, and 1 liver) ranging in age from 9 months to 19 years were diagnosed with HAdV infection (Table 1). Patients presented with varied symptoms from 12 to 912 days post-transplant. Peak HAdV viral load ranged from 37, 000 to >1, 000, 000 copies/mL. All patients had disseminated disease with evidence of graft involvement and varying degrees of acute kidney injury (AKI) making them candidates for BCV therapy over cidofovir to avoid nephrotoxicity. Three out of four patients received cidofovir prior to conversion to BCV. IRB-approved compassionate use of BCV was dosed at 2 mg/kg (max 100 mg) twice weekly PO along with reduced immunosuppression. Resolution of symptoms and HAdV viremia was seen at a mean of 21.5 days (range 15–32) of therapy. All patients had resolution of AKI with a return to baseline creatinine after therapy. Conclusions: Though HAdV infection in pediatric SOT patients is uncommon, a subset of patients experience severe disease, morbidity, and graft loss. Currently, HAdV is not routinely monitored in pediatric SOT transplant patients. Although supportive care and decreased immunosuppression remain as the most important component of therapy, BCV was well tolerated and efficacious in our series. Further research is needed to better understand risk factors for HAdV infection and potential antiviral treatment options to improve patient outcomes.